Kepemimpinan Kepala Sekolah - Hafiizhu Tasyah; Najlaa Zafendi; Riska Masyithah Yendri (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study explores the strategic role of school principals in improving teacher performance, managing resources, and fostering a positive work environment. Principals act as motivators and innovators, utilizing technology for more effective supervision and administration. Challenges such as limited facilities and teacher quality are addressed through adaptive strategies, training, and collaborative supervision. The study recommends strengthening principals' leadership, enhancing teacher professionalism, and optimizing technology to improve education quality in primary schools.